(untitled) (Terr@ Plural, 2012)
This study traces how entertainment patterns have changed among residents in the Mexican border city of Ciudad Juarez, Mexico, as a result of crime and public insecurity. The document is based on empirical research conducted among College students in Ciudad Juarez. Since most of the entertainment activities in this region are addressed to young people, the research group decided to take College Students from the largest public university in the city as the main focus for data collection because they provide sufficient representativeness of the young population living in the different geographic locations in the city.Research findings suggest that as a result of crime and public insecurity, there exists a tendency among the young population to cross into the USA in order to search for entertainment. Nevertheless, crime and insecurity have not modified the entertainment preferences of foreign visitors.Data results found by this study also suggest that the two preferred entertainment activities in Ciudad Juarez are attending to restaurants and also to bars. Such results imply that the levels of education in the city are not a factor that modifies the search of entertainment itself, and there exists a very simple entertainment culture among local population. Further research should be dedicated to find out in what degree such dominant preferences for eating and drinking have limited the development of other cultural activities and the diversification of the entertainment sector along the Northern Mexican Border cities.